X-Linked Lymphoproliferative Disease Type 1: A Clinical and Molecular Perspective - Panchal, Neelam; Booth, Claire; Cannons, Jennifer L.; Schwartzberg, Pamela L. (Frontiers in Immunology, 2018)
X-linked lymphoproliferative disease (XLP) was first described in the 1970s as a fatal lymphoproliferative syndrome associated with infection with Epstein Barr virus (EBV). Features include hemophagocytic lymphohistiocytosis (HLH), lymphomas, and dysgammaglobulinemias. Molecular cloning of the causative gene, SH2D1A, has provided insight into the nature of disease, as well as helped characterize multiple features of normal immune cell function. Although XLP Type 1 (XLP1) provides an example of a primary immunodeficiency in which patients have problems clearing primarily one infectious agent, it is clear that XLP1 is also a disease of severe immune dysregulation, even independent of EBV infection. Here, we describe clinical features of XLP1, how molecular and biological studies of the gene product, SAP, and the associated SLAM family receptors have provided insight into disease pathogenesis including specific immune cell defects, and current therapeutic approaches including the potential use of gene-therapy. Together, these studies have helped change the outcome of this once almost uniformly fatal disease.